Gender anomalies in Stated Preference surveys – Are biases really gender dependent? - Jacob Ladenburg; Søren Bøye Olsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
In this paper, we develop a North-South endogenous growth model to examine thrThe potential for a number of common but severe biases in stated preference method surveys being gender dependent has been largely overlooked in the literature. In this paper we summarize results from three Choice Experiment studies that find evidence in favor of gender differences in vulnerability to biases. Specifically, the results indicate that women are more susceptible to starting point bias than men, while men are more susceptible to hypothetical bias than women. This seems to be interrelated with women inherently being more uncertain than men when choosing from a choice set. Furthermore, we set up a novel theoretical model, which provides an explanation for gender specific susceptibility to biases. We conclude that biases can indeed be gender dependent. Hence, researchers should not simply disregard potential gender differences, but rather take them into account and examine the extent of them when performing surveys. Finally, we give suggestions for future research in this area.
Keywords: J16; D80; Q51; 330; Choice Experiment; Gender; Hypothetical bias; Preference Uncertainty; Starting point bias